His/Met heme ligation in the PioA outer membrane cytochrome enabling light-driven extracellular electron transfer by Rhodopseudomonas palustris TIE-1. (16th June 2020) - Li, Dao-Bo; Edwards, Marcus J; Blake, Anthony W; Newton-Payne, Simone E; Piper, Samuel E H; Jenner, Leon P; Sokol, Katarzyna P; Reisner, Erwin; Van Wonderen, Jessica H; Clarke, Thomas A; Butt, Julea N
Abstract: A growing number of bacterial species are known to move electrons across their cell envelopes. Naturally this occurs in support of energy conservation and carbon-fixation. For biotechnology it allows electron exchange between bacteria and electrodes in microbial fuel cells and during microbial electrosynthesis. In this context Rhodopseudomonas palustris TIE-1 is of much interest. These bacteria respond to light by taking electrons from their external environment, including electrodes, to drive CO2 -fixation. The PioA cytochrome, that spans the bacterial outer membrane, is essential for this electron transfer and yet little is known about its structure and electron transfer properties. Here we reveal the ten c -type hemes of PioA are redox active across the window +250 to −400 mV versus Standard Hydrogen Electrode and that the hemes with most positive reduction potentials have His/Met and His/H2 O ligation. These chemical and redox properties distinguish PioA from the more widely studied family of MtrA outer membrane decaheme cytochromes with ten His/His ligated hemes. We predict a structure for PioA in which the hemes form a chain spanning the longest dimension of the protein, from Heme 1 to Heme 10. Hemes 2, 3 and 7 are identified as those most likely to have His/Met and/or His/H2 O ligation. Sequence analysis suggests His/Met ligation of Heme 2 and/or 7 is a defining feature of decaheme PioA homologs from over 30 different bacterial genera. His/Met ligation of Heme 3 appears to be less common and primarily associated with PioA homologs from purple non-sulphur bacteria belonging to the alphaproteobacteria class.